Wintertime Particulate Matter Decrease Buffered by Unfavorable Chemical Processes Despite Emissions Reductions in China. Issue 14 (13th July 2020) - Leung, Danny M.; Shi, Hongrong; Zhao, Bin; Wang, Jing; Ding, Elizabeth M.; Gu, Yu; Zheng, Haotian; Chen, Gang; Liou, Kuo‐Nan; Wang, Shuxiao; Fast, Jerome D.; Zheng, Guangjie; et al.
Abstract: Extreme and persistent haze events frequently occur during wintertime China. While recent emissions reductions reduced annual mean fine particulate matter (PM2.5 ) concentrations over eastern China, their effectiveness on wintertime PM2.5 trend remains uncertain. We use observations and model simulations to quantify seasonal differences in PM2.5 trends and investigate the underlying chemical mechanisms driving such differences. We find a much slower decrease in observed wintertime PM2.5 (−3.2% yr −1 ) since 2014, in contrast to a drastic summertime decrease (−10.3% yr −1 ). Simulations show two previously underappreciated mechanisms buffering wintertime PM2.5 decrease, including an increase in oxidation capacity due to nitrogen oxides (NO x ) reductions under wintertime volatile organic compound (VOC)‐limited chemistry, and an enhanced conversion of nitric acid to nitrate by ammonia due to sulfur dioxide reductions. Our findings suggest that control policies targeting VOC and deep NO x reductions are needed to improve wintertime PM2.5 air quality over China. Plain Language Summary: Severe wintertime particulate matter (PM) pollution in China is an important environmental problem causing hundreds of thousands of deaths annually. Recent emissions reductions have gradually improved annual mean PM air quality in eastern China. However, our observational analysis unexpectedly shows a much weaker decrease in PM during winter compared with other seasons. State‐of‐the‐art model simulations suggest that the weakened wintertime PM decline is mainly attributed to the increase in wintertime atmospheric oxidation capacity and the enhanced conversion of nitric acid to nitrate by ammonia, which are induced by anthropogenic emission reductions. Our findings indicate that previous pollution control policies did not effectively mitigate severe wintertime PM pollution due to these unfavored chemical processes. Stricter control policies targeting oxidants and wintertime emission sources are imperative to counteract the buffering chemical mechanisms over China. Key Points: We show a slower decrease in observed PM2.5 over China in winter (−3.2% yr −1 ) compared with summer (−10.3% yr −1 ) since 2014 Simulations show this is because wintertime NO x reductions under VOC‐limited chemistry cause an increase in secondary PM2.5 formation Sulfur dioxide reductions also cause an enhanced conversion of nitric acid to particulate nitrate by ammonia